Experimental encephalitis caused by Taenia crassiceps cysticerci in mice Encefalite experimental causada por cisticercos de Taenia crassiceps em camundongos - Hidelberto Matos-Silva; Bruno Pereira Reciputti; Élbio Cândido de Paula; André Luiz Oliveira; Vânia Beatriz Lopes Moura; Marina Clare Vinaud; Milton Adriano Pelli Oliveira; Ruy de Souza Lino-Júnior (Arquivos de Neuro-Psiquiatria)
OBJECTIVES: To present the experimental model of neurocysticercosis (NCC) caused by Taenia crassiceps cysticerci, to describe the inflammatory process, susceptibility, or resistance of BALB/c and C57BL/6 mice to this infection, and to describe the host-parasite relationship. METHODS: The animals were intracranially inoculated with initial stage T. crassiceps cysticerci. They were euthanized at 7, 30, 60, and 90 days after the inoculation. Their encephala were removed for the histopathologic analysis, classification of the parasites, and inflammatory lesions. RESULTS: Experimental NCC was observed on both mice lineages. BALB/c mice presented inflammatory lesions with greater intensity, inducing necrosis on late stage parasites, and with an acute inflammation pattern, while C57BL/6 mice showed greater capability on provoking early necrosis in the cysticerci, which showed a chronic inflammation pattern. CONCLUSIONS: This experimental model induced NCC on mice with characteristic inflammation and lesions. C57BL/6 mice were able to induce precocious necrosis of the parasites presenting inflammatory lesions with lower intensity. OBJETIVOS: Apresentar o modelo experimental de neurocisticercose (NCC) com cisticercos de Taenia crassiceps, descrever a inflamação, suscetibilidade e resistência em camundongos BALB/c e C57BL/6, caracterizando melhor a relação parasito-hospedeiro. MÉTODOS: Os animais foram inoculados intracranialmente com cisticercos de T. crassiceps em estádio inicial e eutanasiados aos 7, 30, 60 e 90 dias após a infecção. Retiraram-se os encéfalos para análise histopatológica, classificação dos parasitos e lesões inflamatórias. RESULTADOS: Foi possível induzir NCC nas duas linhagens de camundongos utilizados como modelo experimental. Os animais BALB/c apresentaram lesões inflamatórias mais intensas do que os camundongos C57BL/6 e induziram nos parasitos necrose na fase tardia com padrão inflamatório agudo. Os C57BL/6 mostraram-se mais hábeis em provocar necrose precocemente nos cisticercos, mas com padrão inflamatório crônico. CONCLUSÕES: Este modelo experimental induziu NCC nos animais com inflamações e lesões. Os camundongos C57BL/6 foram hábeis em induzir precocemente necrose nos parasitos, apresentando lesões inflamatórias com menor intensidade.